2019
DOI: 10.3390/w11122590
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Violent Sloshing with Water Jet Flows by Using the ISPH Method

Abstract: The smoothed particle hydrodynamics (SPH) method has been playing a more and more important role in violent flow simulations since it is easy to deal with the large deformation and breaking flows from its Lagrangian particle characteristics. In this paper, the incompressible SPH (ISPH) method was used to simulate the liquid sloshing in a 2D tank with water jet flows. The study compares the liquid sloshing under different water jet conditions to analyze the effects of the excitation frequency and the water jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Thiagarajan et al [14] carried out numerical investigations on sloshing motions in a twodimensional tank with fill-levels varying from 10% to 95% of the tank height, an oscillation frequency range of 0.35 Hz to 1.25 Hz, and a peak-to-peak displacement of 0.25 m. Utilising the finite-volume method coupled with the VOF technique, the computational results for free-surface elevation and impact pressure were found to be in good agreement with the experimentation. Good agreements could also be found for meshless numerical solutions based on smoothed particle hydrodynamics (SPH) [15][16][17].…”
Section: Introductionmentioning
confidence: 81%
“…Thiagarajan et al [14] carried out numerical investigations on sloshing motions in a twodimensional tank with fill-levels varying from 10% to 95% of the tank height, an oscillation frequency range of 0.35 Hz to 1.25 Hz, and a peak-to-peak displacement of 0.25 m. Utilising the finite-volume method coupled with the VOF technique, the computational results for free-surface elevation and impact pressure were found to be in good agreement with the experimentation. Good agreements could also be found for meshless numerical solutions based on smoothed particle hydrodynamics (SPH) [15][16][17].…”
Section: Introductionmentioning
confidence: 81%
“…Another study was also presented on the SPH method applied to simulate liquid sloshing in a 2D tank with water jet flows as presented by Jiang et al [43] The study compared the liquid sloshing under different conditions to analyze the effects of excitation frequency and water jet on the impact pressures. Results obtained firstly confirmed the applicability of the SPH method to accurately replicate these features and, secondly, demonstrated that the water jet flows can significantly affect the impact pressures on the wall caused by the violent sloshing [43].…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…This technology is widely used in the cleaning industry and can handle nonregular surfaces, but, as we will soon find out, it consumes a great amount of power and water. Therefore, the key to this technology is nozzle geometry itself [20,21]. In places where water scarcity is a major problem, the use of pressurized water is not only an economical issue, but also an environmental one [18].…”
Section: Introductionmentioning
confidence: 99%